Floral Initiation in Response to Planting Date Reveals the Key Role of Floral Meristem Differentiation Prior to Budding in Canola (Brassica napus L.) - Zhang, Yaofeng; Zhang, Dongqing; Yu, Huasheng; Lin, Baogang; Fu, Ying; Hua, Shuijin (Frontiers in Plant Science, 2016)
In Brassica napus, floral development is a decisive factor in silique formation, and it is influenced by many cultivation practices including planting date. However, the effect of planting date on floral initiation in canola is poorly understood at present. A field experiment was conducted using a split plot design, in which three planting dates (early, 15 Sep, middle, 1 Oct, and late, 15 Oct) served as main plot and five varieties differing in maturity (1358, J22, Zhongshuang 11, Zheshuang 8, and Zheyou 50) employed as subplot. The purpose of this study was to shed light on the process of floral meristem (FM) differentiation, the influence of planting date on growth period (GP) and floral initiation, and silique formation. The main stages of FM developments can be divided into four stages: first, the transition from shoot apical meristem to FM; second, flower initiation; third, gynoecium and androecium differentiation; and fourth, bud formation. Our results showed that all genotypes had increased GPs from sowing to FM differentiation as planting date was delayed while the GPs from FM differentiation to budding varied year by year except the very early variety, 1358. Based on the number of flowers present at the different reproductive stages, the flowers produced from FM differentiation to budding closely approximated the final silique even though the FM differentiated continuously after budding and peaked generally at the middle flowering stage. The ratio of siliques to maximum flower number ranged from 48% to 80%. These results suggest that (1) the period from FM differentiation to budding is vital for effective flower and silique formation although there was no significant correlation between the length of the period and effective flowers and siliques, and (2) the increased number of flowers from budding were generally ineffective. Therefore, maximizing flower numbers prior to budding will improve silique numbers, and reducing FM degeneration should also increase final silique formation. From the results of our study, we offer guidelines for planting canola varieties that differ in maturity in order to maximize effective flower numbers.